5-aminolevulinic acid combined with ferrous ion reduces adiposity and improves glucose tolerance in diet-induced obese mice via enhancing mitochondrial function. Issue 1 (December 2017) - Ota, Urara; Hara, Takeshi; Nakagawa, Hitoshi; Tsuru, Emi; Tsuda, Masayuki; Kamiya, Atsuko; Kuroda, Yasushi; Kitajima, Yuya; Koda, Aya; Ishizuka, Masahiro; Fukuhara, Hideo; Inoue, Keiji; et al.
Abstract Background Mitochondrial dysfunction is associated with obesity and various obesity-associated pathological conditions including glucose intolerance. 5-Aminolevulinic acid (ALA), a precursor of heme metabolites, is a natural amino acid synthesized in the mitochondria, and various types of cytochromes containing heme contribute to aerobic energy metabolism. Thus, ALA might have beneficial effects on the reduction of adiposity and improvement of glucose tolerance through its promotion of heme synthesis. In the present study, we investigated the effects of ALA combined with sodium ferrous citrate (SFC) on obesity and glucose intolerance in diet-induced obese mice. Methods We used 20-weeks-old male C57BL/6J diet-induced obesity (DIO) mice that had been fed high-fat diet from 4th week or wild-type C57BL/6J mice. The DIO mice were orally administered ALA combined with SFC (ALA/SFC) for 6 weeks. At the 4th and 5th week during ALA/SFC administration, mice were fasted for 5 h and overnight, respectively and used for oral glucose tolerance test. After the ALA/SFC administration, the plasma glucose levels, weight of white adipose tissue, and expression levels of mitochondrial oxidative phosphorylation (OXPHOS) complexes were examined. Furthermore, the effects of ALA/SFC on lipid content and glucose uptake were examined in vitro. Results Oral administration of ALA/SFC for 6 weeks reduced the body weight by about 10% and the weight of white adipose tissues in these animals. In vitro, ALA/SFC reduced lipid content in mouse 3T3-L1 adipocytes in a dose dependent manner, and enhanced glucose uptake in 3T3-L1 adipocytes by 70–90% and rat L6 myoblasts by 30% at 6 h. Additionally, oral administration of ALA/SFC reduced plasma glucose levels and improved glucose tolerance in DIO mice. Furthermore, ALA/SFC enhanced the expression of OXPHOS complexes III, IV, and V by 40–70% in white adipose tissues of DIO mice, improving mitochondrial function. Conclusions Our findings indicate that ALA/SFC is effective in the reduction of adiposity and improvement of glucose tolerance, and that the induction of mitochondrial OXPHOS complex III, IV, and V by ALA/SFC might be an essential component of the molecular mechanisms underlying these effects. ALA/SFC might be a useful supplement for obesity and obesity-related metabolic disease such as type 2 diabetes mellitus.